INFLAMMATION OF INTERSTITIAL CONNECTIVE TISSUE SPACE INDUCED BY LEAD ACETATE AND AMELIORATIVE AFTERMATH OF FICUSCARICAON RAT TESTIS - Asad, Ayesha; Hamid, Shabnam; Gul, Afnan; Anwar, Noreen; Bhatti, Dujanah; Waseem, Naureen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe inflammation of interstitial connective tissue space caused by Lead acetate in rat testis and ameliorative after math caused by Ficuscarica. Study Design: Laboratory based experimental study.Place and Duration of Study: Anatomy Department, Army Medical College Rawalpindi together with NIH (National Institute of Health) Islamabad, from Mar to Nov 2017.Methodology: Sprague Dawley male rats, 30 in quantity were chosen and 10 animals each partited into 3 groups. Treatments were given for 8 weeks, once daily. Group A was control group. Group B was treated with dosage of 30 mg/kg of Lead acetate. Group C was given dosage of 30 mg/kg of Lead acetate as well as 80 mg/kg of Ficuscarica. Twenty four hours after the concluding dose, animals were vivisected. For histological study, testis were fixed and stained with Haematoxylin and eosin. Interstitial connective tissue space thickness was morphometrically and assessed by SPSS version 22. A p-value 3 times normal) in group B in comparison to groups A and C. Thickness of space was slightly increased (